The association between vein-to-vein anastomoses and birth weight discordance in relation to placental sharing in monochorionic twin placentas. (February 2022) - Couck, Isabel; Cauwberghs, Brent; Van Aelst, Maïté; Vivanti, Alexandre Joseph; Deprest, Jan; Lewi, Liesbeth
Abstract: Introduction: This study aims to examine the association between the presence and size of a vein-to-vein (VV) anastomosis and birth weight discordance relative to placental discordance in monochorionic diamniotic twin pregnancies. Methods: Placentas of two previous prospective studies were included in this retrospective analysis. After injection with color dye, we measured the placental surface of each twin and VV, artery-to-artery (AA), and artery-to-vein (AV) anastomoses on a digital photograph. We calculated the birth weight ratio (BWR), placental ratio (PR), and birth weight ratio/placenta ratio (BWR/PR), as well as total AV size and net AV transfusion. Placental characteristics were compared between placentas with and without VV anastomoses. We performed univariate analyses to assess the following predictors for BWR/PR: VV size, AA size, total AV size, and net AV transfusion. Multivariate analysis was then performed, including the variables significant in univariate analysis. Results: We analyzed 247 placentas: 58 (23%) with VV anastomoses and 189 without (77%). The BWR and PR were higher in the group with VV. In contrast, BWR/PR was lower in the group with VV anastomoses than in those without. The size of AA anastomoses was larger in placentas with VV anastomoses than in those without. In univariate analysis, VV size and AA size were significantly associated with BWR/PR. However, in multivariate regression, only VV size remained significantly associated with the BWR/PR. Discussion: VV anastomoses are associated with a decreased birth weight discordance relative to the placental sharing discordance, independent of the AA anastomoses. Highlights: A vein-to-vein anastomosis is associated with a decreased birth weight discordance relative to the placental discordance. A vein-to-vein anastomosis appears to lessen the impact of an unequally divided placenta. This effect is independent of the artery-to-artery anastomosis.